IN THE CONTEXT OF DIGITAL TECHNOLOGIES THE CONTENT AND ESSENCE OF MANAGING INDUSTRIAL ENTERPRISES - Ermatova Sahodaton Ismoiljonovna (Zeta Repository, 2023)
This article shows that in the modern period of economic development, the informatization of all spheres of human activity has become very relevant and important. It is emphasized that developing projects and programs aimed at abstracting human labour and replacing it with machine labour is the need of the day. It is shown that in order to achieve development, it is necessary and necessary for any country to introduce digital knowledge and modern information technologies.